A Research on Traceability Technology of Agricultural Products Supply Chain Based on Blockchain and IPFS. (12th November 2021) - Zhang, Lejun; Zeng, Weimin; Jin, Zilong; Su, Yansen; Chen, Huiling
Abstract : Blockchain technology, the fundamental technology of Bitcoin, is featured with high transparency, decentralization, traceability, tamperproof nature, and anonymousness. In this thesis, a case study of the traceability of agricultural products is to explain a traceability solution of agricultural products supply chain based on blockchain and IPFS. The latter one is used to store large quantities of transactions data; and the former one is used for the safety of data storage and circulation. And consumers can know the quality of agricultural products in the shortest time through the evaluation function. As shown in the experiment, the solution is more efficient and secure compared with existing supply chain traceability methods, meeting the traceability requirements of security, transparency, and reliability. Furthermore, the traceability, safety, and performance of the scheme are also analyzed here.